Is there an Association between the Gingival Phenotype and the Width of Keratinized Gingiva? A Systematic Review - Elpiniki Vlachodimou (Dentistry Journal, 2021)
The concept of gingival phenotype and width of keratinized gingiva influencing the diagnosis and treatment in the periodontal scenario is relatively new. Soft and hard tissue dimensions of oral tissues are considered essential parameters in daily clinical practice. Factors such as the biotype category and the width of the keratinized gingiva help dentists seek the perfect therapy plan for each patient to achieve long-term stability of periodontal health. Several methods have been proposed to categorize phenotypes and each phenotype is characterized by various clinical characteristics. This review aims to discuss the possible association between the gingival phenotype and the width of keratinized gingiva along with the results appeared. After a rigorous search in major electronic databases, the results of the included studies indicated that the width of keratinized gingiva seems to be associated with the periodontal phenotype, with thick biotypes being characterized by a more pronounced keratinized gingival width. However, the heterogeneity of the included studies did not allow to make a conclusion about a direct relationship.